Identification of processed pseudogenes in the genome of Thoroughbred horses: Possibility of gene‐doping detection considering the presence of pseudogenes. (25th January 2022) - Tozaki, Teruaki; Ohnuma, Aoi; Kikuchi, Mio; Ishige, Taichiro; Kakoi, Hironaga; Hirota, Kei‐ichi; Kusano, Kanichi; Nagata, Shun‐ichi
Abstract: Processed pseudogenes, also known as retrocopy genes, are copies of messenger RNAs that have been reverse transcribed into DNA and inserted into the genome. In this study, we identified 62 processed pseudogene candidates as intron‐less genes from whole‐genome sequencing (WGS) data of Thoroughbred horses using delly structural variation software. The 62 processed pseudogene candidates were confirmed by PCR amplification of intron‐less products. A total of 11 processed pseudogenes were confirmed in the genome of all 23 analysed horses, whereas three processed pseudogenes with structures of ATP11B, DPH3 and RPL17 were detected in only one of 115 horses by PCR amplification of intron‐less products. Currently, most of the gene doping tests proposed in human and horse sports are adapted PCR‐based methods using hydrolysis probes to detect exon/exon junctions in transgenes because the operation is simple and economical. However, when the pseudogene is present in the host genome, the PCR‐based methods may have a potential risk of detecting false positives. In this study, because processed pseudogenes that exist less frequently in the horse genome may affect PCR‐based transgene detection in gene‐doping tests, we propose and demonstrate that PCR amplification and sequencing using primers designed on transgene and promotors and/or polyadenylation signal for gene expression are useful for gene‐doping detection as an additional confirmatory test to prevent false positives.